The Effect of Hygiene-Based Lymphedema Management in Lymphatic Filariasis-Endemic Areas: A Systematic Review and Meta-analysis. - Meredith E Stocks; Matthew C Freeman; David G Addiss (PLoS Neglected Tropical Diseases)
Background Lymphedema of the leg and its advanced form, known as elephantiasis, are significant causes of disability and morbidity in areas endemic for lymphatic filariasis (LF), with an estimated 14 million persons affected worldwide. The twin goals of the World Health Organization's Global Program to Eliminate Lymphatic Filariasis include interrupting transmission of the parasitic worms that cause LF and providing care to persons who suffer from its clinical manifestations, including lymphedema-so-called morbidity management and disability prevention (MMDP). Scaling up of MMDP has been slow, in part because of a lack of consensus about the effectiveness of recommended hygiene-based interventions for clinical lymphedema. Methods and findings We conducted a systemic review and meta-analyses to estimate the effectiveness of hygiene-based interventions on LF-related lymphedema. We systematically searched PubMed, Embase, ISI Web of Knowledge, MedCarib, Lilacs, REPIDISCA, DESASTRES, and African Index Medicus databases through March 23, 2015 with no restriction on year of publication. Studies were eligible for inclusion if they (1) were conducted in an area endemic for LF, (2) involved hygiene-based interventions to manage lymphedema, and (3) assessed lymphedema-related morbidity. For clinical outcomes for which three or more studies assessed comparable interventions for lymphedema, we conducted random-effects meta-analyses. Twenty-two studies met the inclusion criteria and two meta-analyses were possible. To evaluate study quality, we developed a set of criteria derived from the GRADE methodology. Publication bias was assessed using funnel plots. Participation in hygiene-based lymphedema management was associated with a lower incidence of acute dermatolymphagioadenitis (ADLA), (Odds Ratio 0.32, 95% CI 0.25-0.40), as well as with a decreased percentage of patients reporting at least one episode of ADLA during follow-up (OR 0.29, 95% CI 0.12-0.47). Limitations included high heterogeneity across studies and variation in components of lymphedema management. Conclusions Available evidence strongly supports the effectiveness of hygiene-based lymphedema management in LF-endemic areas. Despite the aforementioned limitations, these findings highlight the potential to significantly reduce LF-associated morbidity and disability as well as the need to develop standardized approaches to MMDP in LF-endemic areas.